Association of Achieving Lupus Low Disease Activity State Fifty Percent of the Time With Both Reduced Damage Accrual and Mortality in Patients With Systemic Lupus Erythematosus. Issue 3 (27th February 2020) - Sharma, Chanakya; Raymond, Warren; Eilertsen, Gro; Nossent, Johannes
Abstract : Objective: To assess the impact of achieving Lupus Low Disease Activity State ≥50% of the time (LLDAS‐50) on damage accrual and mortality in an inception cohort of patients with systemic lupus erythematosus (SLE). Methods: We used data from the Tromsø Lupus Cohort, a longitudinal population‐based study of all patients with SLE in the 2 northernmost counties in Norway. LLDAS was defined as 1) a Systemic Lupus Erythematosus Disease Activity Index 2000 score of ≤4, with no activity in major organ systems, 2) no new features of lupus disease activity, 3) current therapy with prednisolone (or equivalent) dosage of ≤7.5 mg daily, and 4) well‐tolerated standard maintenance dosages of immunosuppressive drugs. Results: A total of 69 patients (33.5%) spent at least half of their follow‐up time in LLDAS (thus, achieving LLDAS‐50) and had significantly better survival and lower risk of developing severe damage over time, according to the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index. After correcting for age and sex, LLDAS‐50 was associated with a significant reduction in risk of having severe damage (hazard ratio [HR] 0.37 [95% confidence interval (95% CI) 0.19–0.73], P < 0.01), and also a reduction in mortality (HR 0.31 [95% CI 0.16–0.62], P < 0.01). Conclusion: Our study validates the findings of the inception cohort by demonstrating that achievement of LLDAS‐50 is associated with a significant reduction in severe damage and, for the first time, demonstrates a reduction in mortality.